Renewable energy desalination; a sustainable approach for water scarcity in ‎arid lands - Farbod Esmaeilion; Abolfazl Ahmadi; Siamak Hoseinzadeh; Mehdi Aliehyaei; Seyed Ali Makkeh; Davide Astiaso Garcia (International Journal of Sustainable Engineering, 2021)
Global warming and population growth have been contributing factors to the decline of freshwater resources around the globe. More than 45% of the desalination plants are in the Middle East. Due to the severe scarcity of freshwater resources, Iran also needs to construct several desalination plants, since by 2021 the ratio of freshwater per capita in the country to the world average per capita will be 0.8. The uses of solar, wind, geothermal, and wave are practical in desalination systems. The average solar radiation in Iran is 15.3 kWh/m2/day, which includes more than 2800 hours of radiation ‎per year in central regions.‎ Also wind, geothermal, and wave energy potentials are equalled to 100$$ × $$106 MW, 200 MW, and 20 kW/m, respectively. The purpose of this paper is to evaluate the feasibility of using renewable energy for desalination in arid and semi-arid regions and Iran has been considered as a case study.